Photo-Fenton catalyst embedded in photothermal aerogel for efficient solar interfacial water evaporation and purification - Xiaoyun Hu; Jianhua Zhou; Xiaojiang Mu; Chengpeng Qiu; Meng Kang; Zhixiang Zhang; Jie Gao; Jing Liu; Lei Miao (Green Carbon, 2025)
Solar steam generation is used for the production of clean water through evaporation. However, during evaporation, high-boiling organic compounds tend to concentrate in the mother liquor, whereas low-boiling organic compounds evaporate with the steam. In this study, a strategy for full-spectrum solar utilization, in which solar steam generation is coupled with photo-Fenton catalysis, was demonstrated for the production of clean water while treating complex wastewater containing high concentrations of organic pollutants. A highly efficient Fenton catalyst, PB/rGO/PPy powder, was developed by integrating Prussian blue (PB), polypyrrole (PPy), and reduced graphene oxide (rGO). The catalyst offers functionality in Fenton catalysis, photothermal conversion, and photogenerated charge transfer channels. It can degrade 95.2% of methyl orange (MO) in 20 min, with a degradation rate constant of 0.251 min−1. Impressively, a PB/rGO/PPy/PVA composite aerogel was created using porous and water-absorbent polyvinyl alcohol (PVA) as a skeleton, where the degradation ability of MO in both deionized water and wastewater reached 100% under 1-sun irradiation, along with an evaporation rate of 1.62 kg m−2 h−1. This integrated aerogel evaporator can be utilized for producing clean water and treating wastewater containing organic pollutants, which may open new avenues for green technologies with high solar energy utilization efficiencies.